A new milliped of the genus Stenozonium Shelley 1998 from Washington State, U. S. A.: first record of the genus and family from North of the Columbia River (Polyzoniida: Polyzoniidae) - Shelley, Rowland M.; Shear, William A. (Zootaxa, 2005)
The new species, Stenozonium leonardi, the northernmost representative of the Polyzoniidae in western North America and the only one north of the Columbia River, is described from the Olympic Peninsula of Washington; it is isolated by some 180 mi (288 km) from S. benedictae Shelley, 1998, in coastal Oregon. Stenozonium alone among the four polyzoniidan genera in western North America consists of entirely allopatric and widely separated species, with one apiece in California, Oregon, and Washington-evidence that it diversified earlier than its ordinal counterparts.